PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMANFAATAN PEKARANGAN UNTUK PENANAMAN TANAMAN BUAHAN PADA MASYARAKAT OHOI NGEFUIT, KECAMATAN KEI BESAR SELATAN BARAT, KABUPATEN MALUKU TENGGARA, MALUKU - Lopulalan, Cynthia Gracia C; Mairuhu, Dedy; Sapulette, Alvian; Waileruny, Welem; Wattimena, Seftnah J; Malakauseya, Jeffrie; Pelasula, Berthy; Mailoa, Meitycofrida (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Wira Wacana Sumba, 2025)
ABSTRACT The purpose of community service activities in Ohoi (Village) Ngefuit, Kei Besar District, Southeast Maluku Regency, Maluku Province is to provide counseling and training on cultivating fruit plants in yards while explaining the benefits of fruit for health. Communities far from the city center are state assets that must be maintained, fostered, and trained to minimize the backwardness that occurs. Rambutan and longan have good adaptability, so they are easy to plant in the yards of farmer groups. The close planting location allows maximum care, so it is expected to provide good results. The process of sharing knowledge and mentoring in PkM activities is an important thing that academics due to the community as part of implementing science and knowledge. Key words: Community empowerment; counseling; training; fruit plants